Nursing diagnoses in relation to women in situations of legal abortion - Santos , Leticia de Araujo Farias dos; Santos , Luzinete Nunes dos; Ohara , Elisabete Calabuig Chapina (Seven Editora, 2023)
INTRODUCTION: Abortion means the interruption of pregnancy, whether spontaneous or provoked. Abortion consists of the interruption of pregnancy up to the 20th or 22nd week, or when the estimated weight of the fetus is up to 500 grams, and there is still another option advocated by other doctors that when the fetus measures up to 16.5 cm. In cases where the management poses a risk to the woman's life, and legal abortion is allowed, it is necessary to have a humanized reception, information where the woman will evaluate whether she should continue with the pregnancy. OBJECTIVES: To describe the competencies of nurses in the delivery room in relation to women in situations of legal abortion and to identify the main Nursing Diagnoses, Expected Outcomes and Nursing Interventions. METHODOLOGY: This was an integrative literature review; To obtain data collection and selection of articles, the following databases were used: Latin American and Caribbean Health Sciences Literature (LILACS), BDENF nursing (Brazil), Scientific Electronic Library Online (SCIELO) and Ministry of Health. The guiding question for the elaboration of the integrative review was: What are the competencies of the nurse in the delivery room in relation to women in situations of legal abortion? A search of the articles was carried out using the descriptors in Portuguese according to DeCS (Descriptors in Health Sciences): Legal Abortion, Nursing, Care, Competence. RESULTS: Applying the established criteria, nineteen (29) scientific articles were obtained for the integrative review for analysis. From the survey of articles about the competencies of nurses in nursing care in the process of abortion, it was possible to observe humanization and comprehensiveness in nursing care. Among the nursing diagnoses, we list: Decision conflict; Role performance; Anxiety; Hope, fear; Family process; Grief and Death. FINAL CONSIDERATIONS: It is concluded that women faced with a legal abortion need a humanized, ethical approach, having as guiding principles the equality, freedom, and dignity of the human person. The identification of nursing diagnoses contributes to nursing planning and intervention directed to each woman, which is essential for obtaining better quality care. DOI:https://doi.org/10.56238/interdiinovationscrese-060